The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.3109/0284186x.2010.529461
|View full text |Cite
|
Sign up to set email alerts
|

Do patients with lung cancer benefit from physical exercise?

Abstract: Background. Patients with lung cancer are often burdened by dyspnoea, fatigue, decreased physical ability and loss of weight. Earlier studies of physical exercise of patients with COPD have shown promising results. The aim of this study was to investigate, if a well-documented COPD rehabilitation protocol can improve physical fi tness and quality of life (QoL) in patients with lung cancer. Material and methods. Forty-fi ve patients, with a minimum walking distance of 50 meters, absence of cognitive defi cits o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
1
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 16 publications
0
62
1
8
Order By: Relevance
“…Therefore, provision of the appropriate treatment and care programs for controlling the disease and improving the patient QOL remains a fundamental issue. A multidimensional therapeutic approach is recommended including pulmonary rehabilitation (6,7) and an adequate level of physical activity (8,9) in order to improve exercise tolerance, health-related QOL as well as surgical candidacy and to decrease surgical morbidity. Recent studies have shown that physical activity may have important benefits on lung cancer patients and survivors (10)(11)(12), regardless of the disease stage (13) or limited physical activity (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, provision of the appropriate treatment and care programs for controlling the disease and improving the patient QOL remains a fundamental issue. A multidimensional therapeutic approach is recommended including pulmonary rehabilitation (6,7) and an adequate level of physical activity (8,9) in order to improve exercise tolerance, health-related QOL as well as surgical candidacy and to decrease surgical morbidity. Recent studies have shown that physical activity may have important benefits on lung cancer patients and survivors (10)(11)(12), regardless of the disease stage (13) or limited physical activity (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Although the few studies with lung cancer patients have not revealed any consistent results, [4][5][6][7] we recommend these patients regularly spend at least 150 minutes per week (spread out over 5 days) in physical, aerobic, and resistance training, either combined or separately, and supervised at first. The few studies made with this population were not sufficient and well-enough designed for us to conclude that exercising does not help with the symptoms of the disease, with the fatigue, and with their quality of life.…”
Section: Recommendationmentioning
confidence: 91%
“…Diğerleri ise cerrahi girişime uygun olan hastalarda ameliyat öncesi (23)(24)(25)(26)(27), ya da sonrası dönemde egzersiz eğitiminin ön planda olduğu araştırmalardır (14,(28)(29)(30)(31). Birkaçında ileri evre akciğer kanserinde hastane içi PR uygulamaları da yapılmıştır (32)(33)(34). Bu araştırmaların hiçbirinde kontrol grubu yoktur (14,(23)(24)(25)(26)(27)(28)(29)(30)(31).…”
Section: Introductionunclassified
“…Bu araştırmaların hiçbirinde kontrol grubu yoktur (14,(23)(24)(25)(26)(27)(28)(29)(30)(31). Hasta sayıları azdır (24,25,27,28,(30)(31)(32)34). Hepsinin birleştiği ortak nokta, hastaların egzersiz kapasitelerinin artmasıdır.…”
Section: Introductionunclassified
See 1 more Smart Citation